Tuberculous Otomastoiditis. Case Report and Literature Revision - Díez, L. (2008)
Tuberculous otitis media (TOM) is a rare cause of chronic suppurative infection, that occurs in less than 1% of chronic infections of the ear. The clinical findings are variable, so the index of suspicion is low and this will cause a delayed diagnosis and possible complications. Tuberculous otitis media should be considered in all cases of chronic supurative otitis media unresponsive to the usual therapies. A case report of a child and review of the literature are presented, emphasizing that early diagnosis and treatment of TOM can prevent the possible complications.